STUDI KASUS TENTANG AKIBAT DARI BULLYING YANG DILAKUKAN OLEH KONSELI DI SMK NEGERI 1 AMPEK ANGKEK - Ema Tami Lestari; Dodi Pasilaputra (JIP: Jurnal Ilmu Pendidikan, 2024)
This research is entitled a case study about a student who bullied a friend in his class at school. Counselees who often bully their classmates feel that this is not a good thing to do. Generally, the problem in this research is how to help clients change their behavior and make clients aware that their actions are not correct. The approach used in this research is qualitative using descriptive methods and the form of research is a case study. In this research, individual counseling was carried out to help solve the client's problems by changing the client's thinking pattern from an irrational one to a rational one using the behavioral counseling approach model.